(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
In this paper, a scientific way to deal with the issue of dispersion of air pollutants produced from a point source with variable breeze speed and consistent expulsion rate is proposed to concentrate in consistent state condition where whirlpool diffusivity coefficients are taken as constants. The strategies for partition of factors and Fourier change have been utilized for the arrangement of the issue.